If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=x+7/6
We move all terms to the left:
1-(x+7/6)=0
We add all the numbers together, and all the variables
-(+x+7/6)+1=0
We get rid of parentheses
-x+1-7/6=0
We multiply all the terms by the denominator
-x*6-7+1*6=0
We add all the numbers together, and all the variables
-x*6-1=0
Wy multiply elements
-6x-1=0
We move all terms containing x to the left, all other terms to the right
-6x=1
x=1/-6
x=-1/6
| -3=a/4-5 | | 3(4m-6)=4 | | -6=b/8-4 | | 12.52w^2-1=0 | | 8x-74/3=4x | | 7x+4-x-2=-16 | | -7=v/3-4 | | 12.5(2w^2)-1=0 | | 13=-3x+2+2x | | -6x-2x-2=-10 | | 1+√9x=5x | | 4=n+1/4 | | 6x-2x+2=10 | | -2=-7+r/8 | | -17=-7+6x | | 2=x+2/2 | | 1/5x+14x-x+8x=0 | | 3x/5*5+(1-3x/5-9/x)*(-2)=106 | | 16p-4=4(2p-2) | | x/3=0.72 | | -6y^2=24y | | (3x+33)/7=3 | | -7x+6=-64 | | (2x-22)/7=-4 | | 0.04(y-6)+0.16y=0.12y-0.09(10) | | r^2+6=22 | | 10x-18x+2x=5x+6x-9x | | 3y+512.34(45-234)=3 | | (2x+22)/6=-2 | | 11+18=n | | m+5/8=1 | | 2(x+5)-4x=3(x-2)-5x+16 |